2016
DOI: 10.1007/s00737-016-0607-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prenatal maternal stress on umbilical cord blood cytokine levels

Abstract: Purpose Prenatal maternal stress (PNMS) is known to influence fetal programming and development. Thus far, the effects of PNMS on the developing immune system have mainly been documented in animal studies. This study aimed to examine the association between PNMS and immune cytokine profiles in the umbilical cord blood of newborn human infants. Methods PNMS, including perceived stress, numbers of stressful life events experiences (both partner and health related), and state and trait anxiety, was assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…Interestingly, some studies have indicated that maternal stress during pregnancy may play a significant role in the development of AD in offspring. It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18–20 years . Possible psycho‐immunological pathways are changes in cytokine levels or oxidative stress transferred by the placenta .…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%
“…Interestingly, some studies have indicated that maternal stress during pregnancy may play a significant role in the development of AD in offspring. It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18–20 years . Possible psycho‐immunological pathways are changes in cytokine levels or oxidative stress transferred by the placenta .…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%
“…For example, studies that have measured interleukin (IL)-6 in cord blood report decreased [117] or unchanged [118,119] IL-6 levels in response to the same prenatal dose of betamethasone. In another study in which second trimester maternal stress perception occurred, IL-6 levels increased [120]. The discrepancies between these studies could reflect the fact that cohorts exposed to antenatal steroids often include preterm neonates, in whom the immune system is still immature, in contrast to prenatally stressed neonates, largely born at term.…”
Section: Consequences Of Fetal Glucocorticoid Exposure On Postnatal Imentioning
confidence: 97%
“…No experimental studies were found; therefore only analytical epidemiological studies were included, which comprised of 27 cohort studies, two case-control studies, and one cross-sectional study. The type of psychosocial stress indicators investigated in the studies included anxiety, [21][22][23][24]27,30,35,36,48,49 depression, [22][23][24]30,35,37,41,42 bereavemet, 29,32,38 work-related stress, 33,36,47,48 and NLEs, 19,20,25,26,28,31,34,39,40,[43][44][45][46]49,50 which were usually comprised of a composite of different indicators of stressors. Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member. Twelve studies assessed the impact of maternal stress on asthma, 20,[27][28][29][30][31][32]34,37,38,42,46 eight studies on atopic eczema/dermatitis, [22][23][24]28,31,44,47,48 ten studies on wheeze, 20,[24][25][26][27][28]30,35,42,43,46 three studies on allergic rhinitis, 24,28,31 three on atopic sensitization, 27,31,42 and six studies on cord blood IgE or cytokines 19,21,36,39,45,50 (Table S1).…”
Section: Study Characteristicsmentioning
confidence: 99%